Ontology-based modelling of extended web service secure conversation pattern. (30th September 2019) - Dwivedi, Ashish Kumar
Securing an application based on Service Oriented Architecture provides defences against a number of security threats arising from exposing applications and data to the internet. Various security guidelines are available to apply security in web applications. But these guidelines are sometimes difficult to understand and generate inconsistencies. In this study, an extended web service secure conversation pattern is presented in the presence of a man-in-the-middle attack. An ontology-based modelling and refinement framework is presented for semantically analysing an extended web service secure conversation pattern. A metamodel is introduced to provide rigorous modelling of security services in terms of concepts, properties, and relationships. At the end of this study, an evaluation of the proposed approach has been made by performing experiments for security requirements against security policies in presence of proposed description logic rules.